Chorein deficiency promotes ferroptosis - Yoshiaki Nishizawa; Hitoshi Sakimoto; Omi Nagata; Natsuki Sasaki; Yuka Urata; Kaoru Arai; Hanae Hiwatashi; Izumi Yokoyama; Shosei Kishida; Akira Sano; Masayuki Nakamura (FEBS Open Bio)
Ferroptosis is a type of programmed cell death owed to an intracellular accumulation of iron resulting in the generation reactive oxygen species, which in turn can cause peroxidation of plasma membrane lipids and ultimately result in cell death. We investigated the potential involvement of VPS13A deficiency in ferroptosis. The VPS13A gene encodes for chorein, and its deficiency is a molecular cause of chorea‐acanthocytosis (ChAc), a Huntington‐like disease with neurodegeneration in the striatum. In our previous study, we found male infertility characterized by increased malondialdehyde staining of the spermatozoa in the testes of the ChAc model mice. Thus, in this study we performed metabolome analysis of sperm extracted from the epididymis of the ChAc model mice, which revealed decreased cystine levels, suggesting an association between chorein deficiency and ferroptosis. We then investigated the role of chorein in ferroptosis using VPS13A knockdown (VPS13A‐KD) HEK293 cells. We found that VPS13A‐KD cells displayed a significantly diminished resistance to tert‐Butyl hydroperoxide (tBHP)‐induced lipid peroxidation and cell death compared to control cells, which could be rescued by treatment with ferrostatin‐1. Moreover, VPS13A‐KD cells showed Fe(II) accumulation, suggesting an impaired capacity for divalent iron removal. In the cytosolic fraction of VPS13A‐KD cells, the protein level of glutathione peroxidase 4 (GPX4) was significantly reduced, suggesting that dysfunction of chorein impairs GPX4 transport, thereby facilitating ferroptosis. These results suggest that ferroptosis may contribute to neurodegeneration in ChAc caused by loss of chorein function.